2022
DOI: 10.1002/brb3.2688
|View full text |Cite
|
Sign up to set email alerts
|

Parental burnout and sleep problems in Iranian mothers of primary school‐aged children: Exploring the mediation effect of emotional schemas

Abstract: Objectives Sleep is crucial for mental well‐being. Evidence suggests sleep problems in mothers can result from parental burnout. The possible mediators that link parental burnout to sleep problems have not been investigated. This study seeks to explore the mediational role of emotional schemas as psychological constructs, which relate parental burnout to sleep problems in mothers of school‐aged children. Method A total of 224 mothers participated voluntarily in this cross‐sectional study. Data were collected o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…Here, parents' cognitive processing can play a critical role. The findings of Hormozi et al (2022) showed that emotional schemas and individualised beliefs about emotions mediated the relationship between PB and sleep problems (insomnia and hypersomnia). These emotional schemas are shaped by individual-specific experiences such as culture, family environment, and a history of trauma (Edwards 2019).…”
Section: Effects Of Parental Burnout On Parents' Well-beingmentioning
confidence: 94%
“…Here, parents' cognitive processing can play a critical role. The findings of Hormozi et al (2022) showed that emotional schemas and individualised beliefs about emotions mediated the relationship between PB and sleep problems (insomnia and hypersomnia). These emotional schemas are shaped by individual-specific experiences such as culture, family environment, and a history of trauma (Edwards 2019).…”
Section: Effects Of Parental Burnout On Parents' Well-beingmentioning
confidence: 94%
“…Previous studies have shown that parents of autistic children will experience more parental burnout, especially when children have a combination of physical and mental disabilities ( Gérain and Zech, 2018 ; Kütük et al, 2021 ). Chronic parental burnout can affect parents’ physical and mental health, such as increased cortisol, insomnia, overeating, and anxiety, which can decrease their work efficiency ( Brianda et al, 2020 ; Evans et al, 2022 ; Hormozi et al, 2022 ; Exhausted Parents in Japan, n.d. ). Some parents may even resort to alcohol or suicide to avoid parental responsibilities ( Mikolajczak et al, 2019 , 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Kawamoto et al. ( 2018 ) suggested parental burnout is an antecedent for both depression and sleep issues (which are related to depression) (Nutt et al., 2008 ; Kalantar‐Hormozi et al., 2022 ). Parental burnout is manifested as pronounced exhaustion related to one's parental duties.…”
mentioning
confidence: 99%